Відповідь:
Покрокове пояснення:
11 . f( x ) = 1/( x + 1 ) = ( x + 1 )⁻¹ ;
f '( x ) = [ ( x + 1 )⁻¹ ] ' = - 1/( x + 1 )² ; f '( x ) = - 1/( x + 1 )² ;
f '( 1 ) = - 1/( 1 + 1 )² = - 1/4 ; f '( 1 ) = - 1/4 .
12 . y = 2x³ - 6x² - 20 ; D( y ) = R ;
y' = ( 2x³ - 6x² - 20 )' = 6x² - 12x = 6x( x - 2 ) ;
y' = 6x( x - 2 ) ; y' = 0 ; 6x( x - 2 ) = 0 ;
x₁ = 0 ; x₂ = 2 .
Використаємо метод інтервалів : у'(- 1 ) > 0 ; y'( 1 ) < 0 ; y'(3 ) > 0 .
Проміжки зростання : (- ∞ ; 0 ] i [ 2 ;+ ∞ ) ;
проміжок спадання : [ 0 ; 2 ] .
[tex]f(x) = \frac{1}{x + 1} \\ x + 1\neq0 \: \: \: \: \: \: \: \: \: \: x\neq - 1 \\ f'(x) = \frac{(1)'(x + 1) - (x + 1)'}{(x + 1) {}^{2} } = \frac{0(x + 1) - 1}{(x + 1) {}^{2} } = - \frac{1}{(x + 1) { }^{2} } \\ f'(1) = - \frac{1}{(1 + 1) {}^{2} } = - \frac{1}{2 {}^{2} } = - \frac{1}{4} = - 0.25[/tex]
[tex]y = 2 {x}^{3} - 6 {x}^{2} - 20 \\ x \: \epsilon \: R \\ y' = 3 \times 2 {x}^{3 - 1} - 6 \times 2 {x}^{2 - 1} + 0 = 6 {x}^{2} - 12x \\ 6 {x}^{2} - 12x = 0 \\ {x}^{2} - 2x = 0 \\ x(x - 2) = 0 \\ x_{1} = 0 \: \: \: \: \: \: \: \: x_{2} = 2 \\ + + + + [0] - - - - [2] + + + + [/tex]
Промежутки возрастания:
[tex]x \: \epsilon \: ( - \infty ;0]U[2; \: + \infty )[/tex]
Промежуток убывания:
[tex]x \: \epsilon \: [0; \: 2][/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
Покрокове пояснення:
11 . f( x ) = 1/( x + 1 ) = ( x + 1 )⁻¹ ;
f '( x ) = [ ( x + 1 )⁻¹ ] ' = - 1/( x + 1 )² ; f '( x ) = - 1/( x + 1 )² ;
f '( 1 ) = - 1/( 1 + 1 )² = - 1/4 ; f '( 1 ) = - 1/4 .
12 . y = 2x³ - 6x² - 20 ; D( y ) = R ;
y' = ( 2x³ - 6x² - 20 )' = 6x² - 12x = 6x( x - 2 ) ;
y' = 6x( x - 2 ) ; y' = 0 ; 6x( x - 2 ) = 0 ;
x₁ = 0 ; x₂ = 2 .
Використаємо метод інтервалів : у'(- 1 ) > 0 ; y'( 1 ) < 0 ; y'(3 ) > 0 .
Проміжки зростання : (- ∞ ; 0 ] i [ 2 ;+ ∞ ) ;
проміжок спадання : [ 0 ; 2 ] .
11.
[tex]f(x) = \frac{1}{x + 1} \\ x + 1\neq0 \: \: \: \: \: \: \: \: \: \: x\neq - 1 \\ f'(x) = \frac{(1)'(x + 1) - (x + 1)'}{(x + 1) {}^{2} } = \frac{0(x + 1) - 1}{(x + 1) {}^{2} } = - \frac{1}{(x + 1) { }^{2} } \\ f'(1) = - \frac{1}{(1 + 1) {}^{2} } = - \frac{1}{2 {}^{2} } = - \frac{1}{4} = - 0.25[/tex]
12.
[tex]y = 2 {x}^{3} - 6 {x}^{2} - 20 \\ x \: \epsilon \: R \\ y' = 3 \times 2 {x}^{3 - 1} - 6 \times 2 {x}^{2 - 1} + 0 = 6 {x}^{2} - 12x \\ 6 {x}^{2} - 12x = 0 \\ {x}^{2} - 2x = 0 \\ x(x - 2) = 0 \\ x_{1} = 0 \: \: \: \: \: \: \: \: x_{2} = 2 \\ + + + + [0] - - - - [2] + + + + [/tex]
Промежутки возрастания:
[tex]x \: \epsilon \: ( - \infty ;0]U[2; \: + \infty )[/tex]
Промежуток убывания:
[tex]x \: \epsilon \: [0; \: 2][/tex]